Exploring the Nanoworld: Middle School Students Use TRIZ-STEM in Nanotechnology Education - Cavdar, Oylum; Yıldırım, Bekir; Kaya, Esin; Akkus, Adem (Amer Chemical Soc, 2024)
This paper investigated the effect of TRIZ (Teoriya Resheniya Izobretatelskikh Zadatch-Theory of Inventive Problem Solving)-STEM activities customized for nanotechnology education on middle school students' problem-solving, critical thinking, and research inquiry skills. Since STEM requires both multidisciplinary work and problem-solving skills, it was believed that study would enhance the skills possessed by the students studying at elementary schools. It also addressed how TRIZ-STEM activities customized for nanotechnology affected their views on nanotechnology and the nature of engineering. The sample consisted of 59 middle school students recruited using purposive convenience sampling. The study adopted an embedded design, which is a mixed research design involving both quantitative and qualitative data collection tools. The results showed that TRIZ-STEM activities did not affect participants' problem-solving, critical thinking, and research inquiry skills. The difference had a small effect size. However, the results showed that TRIZ-STEM activities helped participants develop positive views on nanotechnology and the nature of engineering. Researchers should conduct long-term studies on this topic while also considering the inclusion of biomimicry principles in their research programs.
Keywords: Nanotechnology; STEM Education; TRIZ; Middle School students; Nanoscience